Occupational Therapist\'s Experience and Viewpoints about Occupational Therapy - Somayyeh Kavousi-Pour; Masoud Fallahi-Khoshknab (University of Social Welfare and Rehabilitation Sciences, 2012)
Objective: Improvement in job is directly related to recognition of the experience and viewpoints of those working in the field. This research was designed to find out the job, educational and clinical experience of the occupational therapists. Materials & Methods: This study is a qualitative research using content analysis. Data collection was done via in-depth semi -structured interviews with 15 occupational therapists working in the rehabilitation clinics in Tehran in 2009. To analyze the data, content analysis and inductive analysis were used... Results: First, we obtained 170 key codes from data analysis .These key codes were categorized into 5 themes including "community's attitude toward occupational therapy's", "job dissatisfaction", "a new and creative sight into occupational therapy", "occupational therapy inappropriate educational system" and "the nature of the occupational therapy". The themes obtained from the occupational therapists' experience showed that how the other members of rehabilitation team, patients and patients' family look at occupational therapy and can directly affect the occupational therapists' job satisfaction, positive experience and sense of worth. Conclusion: Experience of occupational therapists in their job is directly related to their patients 'and coworkers' ideas about their sense of worth this view passes to the occupational therapist directly and indirectly. It can affect the occupational therapists' attitudes, satisfaction and job experience. Instructors and mentors of occupational therapy students can contribute to positive experience and satisfaction of the students from occupational therapy.